2019
DOI: 10.1021/acsomega.9b00130
|View full text |Cite
|
Sign up to set email alerts
|

A FRET-Based Fluorogenic Trehalose Dimycolate Analogue for Probing Mycomembrane-Remodeling Enzymes of Mycobacteria

Abstract: The mycobacterial outer membrane, or mycomembrane, is essential for the viability and virulence of Mycobacterium tuberculosis and related pathogens. The mycomembrane is a dynamic structure, whose chemical composition and biophysical properties can change during stress to give an advantage to the bacterium. However, the mechanisms that govern mycomembrane remodeling and their significance to mycobacterial pathogenesis are still not well characterized. Recent studies have shown that trehal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…In related work, we have now reported a fluorescence‐quenched analogue of TDM, named FRET‐TDM, that reports on the mycomembrane‐remodeling activity of trehalose dimycolate hydrolase (Tdmh) . In addition, the Theriot group have reported the use of fluorophore‐modified TMM analogues (synthesized by CuAAC between O‐AlkTMM‐C7 and azido fluorophores) in an elegant investigation of cell envelope assembly and V snapping in Cglut , which further illustrated O‐linked TMM analogues’ applicability in cellular imaging experiments.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…In related work, we have now reported a fluorescence‐quenched analogue of TDM, named FRET‐TDM, that reports on the mycomembrane‐remodeling activity of trehalose dimycolate hydrolase (Tdmh) . In addition, the Theriot group have reported the use of fluorophore‐modified TMM analogues (synthesized by CuAAC between O‐AlkTMM‐C7 and azido fluorophores) in an elegant investigation of cell envelope assembly and V snapping in Cglut , which further illustrated O‐linked TMM analogues’ applicability in cellular imaging experiments.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…At least two different processes liberate trehalose: ligation of mycolic acids from TMM to arabinogalactan to form AGM and transfer of mycolic acids from TMM to another molecule of TMM to form TDM. Breakdown of TDM by the TDM hydrolase (TDMH) yields TMM and mycolic acids (Holmes et al, 2019; Ojha et al, 2010; Yang et al, 2013), so subsequent use of TMM in the forgoing reactions would also release trehalose. Our metabolic labeling results suggested that all of these processes are active as M. smegmatis adapts to carbon limitation ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the more interesting question, however, is the source of the energetically-expensive TMM building blocks. Breakdown of TDM by TDMH furnishes free mycolic acids and TMM, the latter of which could serve as a donor for sidewall AGM synthesis (Holmes et al, 2019; Ojha et al, 2010). While such a pathway would not require ATP, it would be limited by the amount of TDM loss that can be tolerated without lysis (Ojha et al, 2010; Yang et al, 2013) or reduced resilience to host stress (Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Swarts-group recently reported a similar approach, in which cleavage of a quencher group from a construct containing fluorescein and a DABCYL quencher by the mycomembrane remodeling hydrolase Tdmh, led to a the enhancement of green fluorescence. 113 One downside to all these probes is that they exclusively label metaboli-Organic & Biomolecular Chemistry Review cally active cells. As such, they can only be used to diagnose dividing Mtb and monitor treatment efficacy.…”
Section: Organic and Biomolecular Chemistrymentioning
confidence: 99%